Non-acquired immunodeficiency syndrome defining malignancies in people living with haemophilia and human immunodeficiency virus after direct-acting antiviral era - Minami, Rumi; Mita, Eiji; Fujitani, Junko; Endo, Tomoyuki; Fujii, Teruhisa; Tanaka, Takahiro; Watanabe, Tamayo; Hanai, Jugo; Nojima, Masanori; Kakinuma, Akiko; Ishizaka, Aya; Yotsuyanagi, Hiroshi; et al. (Global Health & Medicine, 2024)
Non-acquired immunodeficiency syndrome-defining malignancies (NADMs) are the crucial cause of mortality in people living with haemophilia and human immunodeficiency virus (PLWHH). We aimed to analyse the types and characters of NADMs in PLWHH after approval of direct-acting antivirals (DAA), considering that most PLWHH are infected with hepatitis C virus (HCV). We conducted a nationwide questionnaire mail survey across 395 HIV core facilities in Japan between May 2022 and February 2023. Eight-year data from 64 respondent hospitals (n = 328 PLWHH; 2015–2022) were collected; 35 NADM cases were identified and analysed. Standardised cancer incidence ratios (SCIRs) were calculated. The median age of PLWHH with NADMs was 51 years (interquartile range: 47–62 years); the SCIR was 2.08 (95% confidence interval [CI]: 1.48–2.90) for all malignancies (including carcinoma in situ). Liver cancer accounted for most NADMs (43% [15/35]). The SCIRs of liver cancer (23.09 [95% CI: 13.92–38.30]) and papillary thyroid cancer (9.38 [2.35–37.50]) significantly increased after adjusting for general Japanese male sex and age. Among PLWHH with liver cancers, 73% (11/15) achieved HCV-sustained virological response. Notably, for patients aged ≤ 50 years, 47% (7/15) were affected by liver cancers, and 27% (4/15) succumbed to NADMs. This study presents the largest survey of NADMs in PLWHH after DAA approval. Our findings emphasised the elevated risk of malignancies in PLWHH, underscoring the need for early cancer screening and preventive measures, particularly against liver cancers, even in younger PLWHH.